Comparative Analysis of Bibliometric, Authorship, and Collaboration Trends Over the Past 30-Year Publication History of the Journal of Orthopaedic Trauma and Injury. Issue 8 (August 2018) - Russell, Arielle F.; Nguyen, Michelle; Bhuiya, Mashuq; Likine, Elive F.; Fischer, James P.; Grassel, Kyle; Groswald, Michael; Kabir, Ryan; Spagna, Sydney; Wright, Serena; Whipple, Elizabeth C.; Kacena, Melissa A.; et al.
Abstract : Objectives: In the scientific and medical field, authorship has become increasingly important for tenure and career advancement in addition to improvement in medical care. It was the purpose of this study to investigate changes in bibliometric variables, authorship, and collaboration trends in the Journal of Orthopaedic Trauma ( JOT ) and Injury over a 30-year period. Methods: A bibliometric analysis was completed for all manuscripts meeting the inclusion criteria and published throughout 1 representative year of each decade over the past 30 years. A total of 444 and 1105 manuscripts for JOT and Injury, respectively, met the inclusion criteria. Standard statistical analyses were performed with nonparametric methods for continuous variables and Pearson χ 2 and Cochran linear trend tests for categorical variables. A P < 0.05 was considered statistically significant. Results: There were significant increases over time in all bibliometric variables for both journals, except in the number of countries and pages in JOT. For JOT, the overall percentage of female first authors increased 2.3 times from 1987 to 2015 ( P = 0.021). The overall percentage of female corresponding authors was 7.3%. For Injury, the overall percentage of female first authors increased 1.5 times ( P = 0.007). The overall percentage of female corresponding authors was 13.1%. Conclusions: Understanding changes in publishing characteristics over time and by region is critical with the rising demands of publishing in academic medicine. JOT and Injury have showed an increase in most variables analyzed. However, female authorship in JOT is climbing at a higher rate than Injury .